2011
DOI: 10.2119/molmed.2011.00141
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Enhancer-Binding Protein 1 (AEBP1) (a Novel Macrophage Proinflammatory Mediator) Overexpression Promotes and Ablation Attenuates Atherosclerosis in ApoE−/− and LDLR−/− Mice

Abstract: /NT-BM ) that received AEBP1 nontransgenic (AEBP1 NT ) BM cells. Our in vivo experimental data strongly suggest that macrophage AEBP1 plays critical regulatory roles in atherogenesis, and it may serve as a potential therapeutic target for the prevention or treatment of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…Lipopolysaccharide has been suggested to suppress cholesterol efflux via induction of AEBP1 expression [46]. It has been reported that AEBP1-transgenic mice with macrophage-specific AEBP1 overexpression exhibit hyperlipidemia and develop atherosclerotic lesions in their proximal aortas, whereas ablation of AEBP1 results in significant attenuation of atherosclerosis [47]. More recently, Huang et al [48] reported that berberine attenuated ox-LDL accumulation and foam cell formation in phorbol 12-myristate 13-acetate-induced macrophages through inhibition of AEBP1.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide has been suggested to suppress cholesterol efflux via induction of AEBP1 expression [46]. It has been reported that AEBP1-transgenic mice with macrophage-specific AEBP1 overexpression exhibit hyperlipidemia and develop atherosclerotic lesions in their proximal aortas, whereas ablation of AEBP1 results in significant attenuation of atherosclerosis [47]. More recently, Huang et al [48] reported that berberine attenuated ox-LDL accumulation and foam cell formation in phorbol 12-myristate 13-acetate-induced macrophages through inhibition of AEBP1.…”
Section: Discussionmentioning
confidence: 99%
“…AEBP1 overexpression in AAA results in the activation of NF-κB/p65 and the consequent upregulation of inflammatory cytokines IL-1β, IL-6, TNFα, and MCP-1, as well as MMP2 and MMP-9, matrix metalloproteinases (MMPs) [25]. In addition, modulation of AEBP1 expression has been implicated in other processes and conditions such as adipogenesis [2,5,6,11,26,27], mammary gland development [28][29][30], macrophage cholesterol homeostasis [8,12,31], inflammation [8,25,28,32], and atherosclerosis [32].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, full‐length AEBP1 is predominantly secreted from smooth muscle cells to the extracellular matrix of mesenchymal cells , while the short isoform of AEBP1 appears to reside in the cytoplasm or nuclei and regulate intracellular signaling . Diverse physiological functions of AEBP1 have previously been reported including the activation of inflammatory processes in macrophages by activating nuclear factor kappa B (NF‐κB) , inhibition of peroxisome proliferator‐activated receptor‐gamma (PPAR‐γ) and liver X receptor alpha (LXRα) , regulation of adipogenesis via phosphatase and tensin homolog deleted from chromosome 10 (PTEN) in preadipocytes , abdominal wall development and lung fibrosis . In mice, the short isoform of Aebp1 rather than the full‐length isoform seems to have the activity of inflammatory processes in macrophages .…”
Section: Introductionmentioning
confidence: 99%